2020
DOI: 10.1002/1878-0261.12639
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism‐associated molecular classification of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a disease with unique management complexity because it displays high heterogeneity of molecular phenotypes. We herein aimed to characterize the molecular features of HCC by the development of a classification system that was based on the gene expression profile of metabolic genes. Integrative analysis was performed with a metadata set featuring 371 and 231 HCC human samples from the Cancer Genome Atlas and the International Cancer Genome Consortium, respectively. All samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 51 publications
8
135
0
Order By: Relevance
“…Therefore, in this study, we determined a lower metabolic level, and that greater tumor heterogeneity of the PCa samples was associated with a worse prognosis for the patient. This was in accordance with that reported for liver cancer (60). These specifications may partly explain why tumors from the C1 subset had the worst prognosis in PCa.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study, we determined a lower metabolic level, and that greater tumor heterogeneity of the PCa samples was associated with a worse prognosis for the patient. This was in accordance with that reported for liver cancer (60). These specifications may partly explain why tumors from the C1 subset had the worst prognosis in PCa.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, C3 displayed intermediate metabolic activity. Our classification in CRC coincided with that in HCC, a work published recently (16). Clinical feature analyses showed that most samples in C2 were in advanced pathological stage.…”
Section: Discussionsupporting
confidence: 81%
“…C2 exhibited high immune infiltration and sensitivity toward immune blockade as well as chemotherapy. What's more, a meaningful 90-gene classifier was provided, which may help to predict the prognosis of HCC patients and prospective therapies (16). However, research on metabolism-relevant molecular classification of CRC has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A univariate Cox proportional hazards regression model assisted in estimating the hazard ratios exhibited by univariate analyses. A two-tailed P value less than 0.05 exhibited statistical signi cance [22].…”
Section: Discussionmentioning
confidence: 98%